Керування антенною системою з механізмом наведення паралельної структури типу «Hexapod» - Паламар, М. І.; Пастернак, Ю. В. (Видавництво Львівської політехніки, 2011)
Розглядається принцип, алгоритм керування антенною системою з механізмом наведення на основі паралельної кінематичної структури Hexapod як опорно-поворотного пристрою. Проаналізовано переваги і недоліки такого поворотного пристрою, створено модель та запропоновано алгоритм керування наведенням антени. This paper considers the principle, algorithm, hardware, and software structure for control of the antenna system with the pointing mechanism based on the parallel cinematic structure «Hexapod» as a supporting-turning device. The advantages and drawbacks of such turning device were analyzed. The computer model of the control system was developed.Аntenna pointing control algorithm was proposed.
Keywords: антенна система; схеми і конструкції АС з ОПП Hexapod; the antenna system; charts and constructions; ACE from OPP Hexapod